Epikeratophakia for aphakia, keratoconus, and myopia. Issue 2 (February 1990) - Halliday, B L
Abstract : A series of 67 cases of epikeratophakia is presented with an average time from surgery of 12.2 months. For aphakia there was a delay in the recovery of vision, but by nine months 83% of 57 patients achieved an acuity equal to, or within 1 line of, the preoperative value. 57% were corrected to within 3 dioptres of emmetropia, but in the latter part of the series 75% were within this range. Astigmatism and reduced contrast sensitivity, especially in the presence of glare, were important complications. For keratoconus, 86% of seven patients with over two months of follow-up achieved a spectacle corrected acuity of 6/9 or better. One patient had surgery for myopia and obtained the desired refractive correction.